2016
DOI: 10.3311/pptr.8523
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Significant Variables Influencing Overtaking Maneuvers on Two-lane, Two-way Rural Roads in Iran

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
1
Order By: Relevance
“…The questionnaire consisted of two parts; the first part contained questions related to demographic questions like gender, age, education, driving experience and occupation, whereas the second part consisted of questions related to both the independent and dependent variables containing the items adapted from Manchester Driver Behavior Questionnaire (Khoso et al, 2011). The same questionnaire was used by other researchers, including Sucha et al (2014) andTavakoli et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire consisted of two parts; the first part contained questions related to demographic questions like gender, age, education, driving experience and occupation, whereas the second part consisted of questions related to both the independent and dependent variables containing the items adapted from Manchester Driver Behavior Questionnaire (Khoso et al, 2011). The same questionnaire was used by other researchers, including Sucha et al (2014) andTavakoli et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to studies conducted in the UK, the DBQ has been used in several international studies, for example, Sweden (32), New Zealand (33), Greece (34), Turkey (35), China (36), Australia (37), Countries of the Arabic golf (38), France (39), Czech Republic (40), Iran (41), and Italy (42). For instance, in the Australian DBQ, Davey et al (37) proposed a modified version of the DBQ consisting of 20 items; all lapse items were omitted because previous research has indicated that this factor is not associated with the occurrence of accidents.…”
Section: Related Workmentioning
confidence: 99%
“…Overtaking represents one of the most serious causes of two-lane two-way rural roads injuries and fatalities; due to its nature, it involves a risk of a head-on collision with oncoming traffic, and therefore it has a direct impact on safety. Previous studies showed that the accident severity resulting from this type of manoeuvre is significantly higher than that of other accident types on two-lane two-way rural roads [11][12][13].…”
Section: Introductionmentioning
confidence: 99%